Anders Sannerstedt, Förhandlingar i riksdagen. Lund: Lund University Press, 1992, 277 s.; Mats Sjölin, Coalition Politics and Parliamentary Power> Lund: Lund University Press, 1993, 230 s. - Damgaard, Erik (Politica, 1993)
Anders Sannerstedt, Förhandlingar i riksdagen. Lund: Lund University Press, 1992, 277 s.; Mats Sjölin, Coalition Politics and Parliamentary Power> Lund: Lund University Press, 1993, 230 s.